Monitoring low birth weight: an evaluation of international estimates and an updated estimation procedure - Ann K. Blanc; Tessa Wardlaw (The World Health Organization, 2005)
OBJECTIVE: To critically examine the data used to produce estimates of the proportion of infants with low birth weight in developing countries and to describe biases in these data. To assess the effect of adjustment procedures on the estimates and propose a modified estimation procedure for international reporting purposes. METHODS: Mothers' reports about their recent births in 62 nationally representative Demographic and Health Surveys (DHS) conducted between 1990 and 2000 were analysed. The proportion of infants weighed at birth, characteristics of those weighed, extent of misreporting, and mothers' subjective assessments of their children's size at birth were examined. FINDINGS: In many developing countries the majority of infants were not weighed at birth. Those who were weighed were more likely to have mothers who live in urban areas and are educated, and to be born in a medical facility with assistance from medically trained personnel. Birth weights reported by mothers are "heaped" on multiples of 500 grams. CONCLUSION: Current survey-based estimates of the prevalence of low birth weight are biased substantially downwards. Two adjustments to reported data are recommended: a weighting procedure that combines reported birth weights with mothers' assessment of the child's size at birth, and categorization of one-quarter of the infants reported to have a birth weight of exactly 2500 grams as having low birth weight. Averaged over all surveys, these procedures increased the proportion classified as having low birth weight by 25%. We also recommend that the proportion of infants not weighed at birth be routinely reported. Efforts are needed to increase the weighing of newborns and the recording of their weights.